UMASKANDI IZIBONGO: SEMANTIC, PROSODIC AND MUSICAL DIMENSIONS OF VOICE IN ZULU POPULAR PRAISES - Pooley, Thomas M. (International Library of African Music, 2016)
Umaskandi izibongo are Zulu popular praises characterized by rapid, tonally nuanced phrases of incisive social comment set to instrumental music. They articulate the experiences, genealogy and heritage of their orators, and are replete with idioms and lyrical encodings intelligible only to those familiar with the contexts, symbols and sounds specific to umaskandi life worlds. Izibongo have been combined with features of Zulu style and idiom to create a hybrid, indigenous genre of popular music. Umaskandi orators articulate shared experiences of poverty, inequality, migrancy and dispossession in South Africa, and often use martial, caustic imagery to evince their social critique. A genealogy of izibongo is offered linking umaskandi to other popular praises, to genres of dance and bow music, and to izibongo zamakhosi, or the praises of kings. From research based on fieldwork in KwaZulu- Natal conducted between 2012 and 2015, the close analysis, transcription and translation of songs by umaskandi artists Phuzekhemisi, Mfaz' Omnyama and Jonathan Mathenjwa offers insight into the style and structure of izibongo. The semantic, prosodic and musical dimensions of voice are explored through graphic representation and analysis in 'Praat'. The analyses demonstrate the complex interplay of speech tone, intonation, rhythm and rate, and how these prosodic features articulate and complicate umaskandi texts. The emphasis on voice complements a literature that has to date focused on its instrumental accompaniment on guitar. The use of digital methods of analysis and transcription offers an alternative to staff notation as a toolset for theorizing African music.
Keywords: Umaskandi Izibongo; Zulu Praises; Umaskandi Music; African Music